2020
DOI: 10.4314/ovj.v9i4.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pimobendan on left atrial function in dogs with preclinical myxomatous mitral valve disease

Abstract: Background: Left atrial (LA) function is an important determinant of the left ventricular (LV) filling, playing a key role in maintaining optimal cardiac performance. Pimobendan is a phosphodiesterase III inhibitor with positive inotropic and vasodilator effects. The present study aims to investigate the effects of pimobendan on LA function in dogs with stage B2 myxomatous mitral valve disease (MMVD). Aim: The aim of this investigation was to study the effects of pimobendan on LA function in dogs with preclini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…This change may alternatively be explained by improvements in ventricular lusitropic function, as our results did show evidence of this effect. The recent study by Sarcinella et al ( 9 ) of DMVD dogs administered pimobendan chronically which found no significant improvements in LA function may be more characteristic of its effect in dogs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This change may alternatively be explained by improvements in ventricular lusitropic function, as our results did show evidence of this effect. The recent study by Sarcinella et al ( 9 ) of DMVD dogs administered pimobendan chronically which found no significant improvements in LA function may be more characteristic of its effect in dogs.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, echocardiographic evaluation of left atrial pump function can be complicated as LA size is strongly influenced by both ventricular function and loading conditions. For instance, there are reports of increased atrial function under pimobendan treatment, as assessed by LA fractional shortening in two recent feline studies ( 7 , 8 ), but no evidence of improvement in dogs with degenerative mitral valve disease (DMVD) ( 9 ). Therefore, we sought to further investigate the effects of pimobendan on the LA in canine DCM by focusing on multiple echocardiographic indicators of size and function.…”
Section: Introductionmentioning
confidence: 99%
“…Патологія серця у тварин може клінічно не проявлятися тривалий час, що створює труднощі для постановки діагнозу (Oldach et al, 2019;Kochie et al, 2020). У разі виявлення у собак серцево-судинної патології важливим є встановити ступінь розладів гемодинаміки, а також захворювання інших органів, що можуть бути вирішальними для перебігу та прогнозу (Tjostheim et al, 2019;Sarcinella et al, 2020). Відомо, що 10 % всіх тварин страждають патологіями серцево-судинної системи різного ступеня вираженості (Zhulikova, 2016;Varkholiak & Gutyj, 2020).…”
Section: вступunclassified